Insights of the Rhynchophorus ferrugineus chemosensory system towards controlling its palm infestation problem: Progress from Omics research and technologies - Kalepu, Rajeswari; Hassan, Maizom; Mohd Assa’ad, Norfarhan; Abdul Hamid, Azzmer Azzar; Nor Muhammad, Nor Azlan (Springer Nature, 2024)
The red palm weevil (RPW), scientifically known as Rhynchophorus ferrugineus, poses a significant threat to various palm species, leading to substantial economic losses in affected countries. The success of R. ferrugineus infestations can be attributed to numerous factors, such as its discreet behaviour, highly chitinized mouthpart, and prolific reproduction. Efforts to control R. ferrugineus, including insecticides, have encountered challenges such as resistance development and environmental harm. Consequently, there is a vital requirement for environmentally friendly chemicals that specifically target R. ferrugineus, with the chemosensory system being a potential focal point. The chemosensory system of the insect, which is crucial to its interaction with its plant host, could provide an effective strategy for preventing infestations. However, current knowledge about R. ferrugineus chemosensory system, including its anatomy, physiology, and relevant receptors or proteins, remains limited. This review aims to compile existing information on the chemosensory system to guide future research initiatives. It highlights the lack of omics-derived data on the chemosensory system of R. ferrugineus. It emphasises the need for a deeper understanding of the structural and functional aspects of related proteins. The review underscores the necessity for comprehensive, multidisciplinary approaches, such as systems biology and computational methods, to unravel the complexities of R. ferrugineus chemosensory system. The review discusses recent findings and seeks to inform and inspire future research endeavours to prevent R. ferrugineus infestations through targeted strategies. In conclusion, omics data available on the chemosensory system of R. ferrugineus is plentiful. This information is a valuable resource that enables analyses to identify potential targets for enhanced pest management strategies.